Biomaterials for stem cell therapy state of art and vision for the future - De Bartolo, Loredana; Bader, Augustinus (CRC Press, 2013)
"Focused on stem cell applications, this book bridges the fields of biomaterials, offering new insights into constructing and regenerating tissues and organs. Its unique feature is linking diseases of the human body to current thinking on how to deal with them in the context of current concepts and technologies by means of an in-depth focus on biomaterials. The book assembles recent advances and covers a range of topics related to stem cell biology, biomaterials and technological approaches such as bioreactors written by top researchers in the field. Stem cells of both embryonic and adult origin are discussed with applications ranging, but not limited to, nerve regeneration, liver, pancreas, skin, trachea, cartilage and bone repair and cardiovascular therapy. Developments in the field reflecting the design and construction of the human body and its principal anatomy are discussed from a materials point of view. The book will be a valuable tool for biomaterial scientists, tissue engineers, clinicians as well as stem cell biologists involved in basic research and applications of adult and embryonic stem cells. It will also be a source of reference for students in biotechnology, biomedical engineering, biology, biochemistry, materials sciences, pharmaceuticals, and veterinary and human medicine"--Provided by publisher.